Husserl and Leibniz: Notes on the Mathesis Universalis - Centrone, Stefania; Da Silva, Jairo Jose [UNESP]; Centrone, S. (Springer, 2017)
The notion of mathesis universalis appears in many of Edmund Husserl's works, where it corresponds essentially to a universal a priori ontology. This paper has two purposes; one, largely exegetical, of clarifying how Husserl elaborates on Leibniz' concept of mathesis universalis and associated notions like symbolic thinking and symbolic knowledge filtering them through the lesson of the so called bohemian Leibniz, Bernard Bolzano; another, more properly philosophical, of examining the role that the universal mathesis is allowed to play, and the space it occupies in Husserl's intuition-based epistemology.
Keywords: Husserl; Leibniz; Bolzano; Mathesis Universalis; Symbolic; Sign